Factors influencing of Ringgit Malaysia / Fhathin Syazwanie Izhar - Izhar, Fhathin Syazwanie (2011)
Purpose: The purpose of the thesis is to investigate the relationship between the Foreign Direct Investment (FDI), Gross Domestic Product (GDI), inflation rate, United State Dollar (US$), interest rate and the movement of Ringgit Malaysia. Besides that, it also to study which is the main factors influencing of Ringgit Malaysia. Background: The reason why government should internalize the Ringgit Malaysia as stated by the Prime Minister, Datuk Seri Najib Razak. Therefore, it needs to know about the factors influence the movement of Ringgit Malaysia. Method: Researcher uses the quarterly data from 1999 to 2009 of the Ringgit Malaysia as the dependent variable, interest rate, inflation rate, gross domestic product and foreign direct investment as independent variable. By having that data, the researcher uses the SPSS and AMOS to find the result. Conclusion: The finding comes out with the four variables selected are significant while only one variable is not significant. Four variables are interest rate. Inflation rate, gross domestic product and foreign direct investment has the positive relationship and only United Stated Dollar detected insignificant relationship toward the movement of Ringgit Malaysia